Shaping African identities through Ubuntu philosophy in proverbs:our daily bread. - Viriri, Advice (2016)
The article closely examines the relationship between ubuntu philosophy and proverbs particularly on the comparative experiences of the construction of identities in African societies. Some people have often used the term philosophy to refer to that which has been written down only. Whether written or not, this docs not take away the philosophicalness of African proverbs and their influence on the African creative genius on the world global stage.The process of philosophical thinking starts when people reflect and question the nature of human existence and its value. This is not a preserve of the West. Proverbs are considered to be the palm oil with which words are eaten. Proverbs, in providing these philosophical statements, become images of thought, sensations, customs and the total experience of a people in all spheres of life like " politics, spirituality, economics, culture and many more. It will be argued here that Africans should be mindful of their oral traditions for this enables them to have a proper direction and be active participants in their own history. A people’s values, attitudes and belief systems determine the content, style, structure, performance and conceptualisation of any form of African oral art, proverbs included. In short, the article will look at proverbs as they condition human imagination in upholding the core values encapsulated in the African spirit of ubuntu.